SEKOLAH TINGGI ASTRONOMI DI KOTA PARE-PARE TEMA ARSITEKTUR METAFORA - Juddah, Shahibuddin; Muthmainnah, Muthmainnah (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2015)
Pare- Pare as a city that deserves to have a facility of science and technology that is intended for younger generations in Pare - Pare in this case the facilities of science and technology relates to astronomy namely the College of Astronomy (Science Astrology) in Pare- pare the theme of Architecture Metaphor. In the field of astronomy there are various kinds of fantastic shapes that can be used as the epitome of form in architecture such as the shape of constellations, planets orbit trajectory shapes and forms of other celestial bodies, as well as the forms of the phenomenon produces. The realization of these forms as a symbol on the style of the building, both buildings form, function and arrangement of space in it, it is hoped the perpetrators of activity in the building feel the intention and expression of the building.